Guaranteed to Bend Your Brain - Poskitt, Kjartan; Illustrated by Dunton, Trevor (London Scholastic Children's Book, 2008)
This work features maths with the laughs added in! How can maths rescue someone in deadly peril? Which famous mathematician was murdered? How did time begin? Find out in "Murderous Maths" - all the tricks, tips and short-cuts they don't teach at school.
Including Illustrations
Keywords: Mathematics